2016
DOI: 10.1111/tpj.13246
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Arabidopsis growth by the allelopathic compound azetidine‐2‐carboxylate is due to the low amino acid specificity of cytosolic prolyl‐tRNA synthetase

Abstract: The toxicity of azetidine-2-carboxylic acid (A2C), a structural analogue of L-proline, results from its incorporation into proteins due to misrecognition by prolyl-tRNA synthetase (ProRS). The growth of Arabidopsis thaliana seedling roots is more sensitive to inhibition by A2C than is cotyledon growth. Arabidopsis contains two ProRS isozymes. AtProRS-Org (At5g52520) is localized in chloroplasts/mitochondria, and AtProRS-Cyt (At3g62120) is cytosolic. AtProRS-Cyt mRNA is more highly expressed in roots than in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
(78 reference statements)
1
17
0
Order By: Relevance
“…Research on plant aaRSs revealed their cellular localization (Rokov-Plavec et al 2008, Duchêne et al 2009, Kekez et al 2016, substrate specificity (Rokov et al 2008, Rokov and Weygand-Durasevic 2009, Rokov-Plavec et al 2002, 2004, Aldinger et al 2012, fidelity (Rokov-Plavec et al 2013, Lee et al 2016, Hoffman et al 2019 and protein interactors (Yang et al 2018, Kekez et al 2019. Thus far, only one crystal structure of plant aaRS is reported (Kekez et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research on plant aaRSs revealed their cellular localization (Rokov-Plavec et al 2008, Duchêne et al 2009, Kekez et al 2016, substrate specificity (Rokov et al 2008, Rokov and Weygand-Durasevic 2009, Rokov-Plavec et al 2002, 2004, Aldinger et al 2012, fidelity (Rokov-Plavec et al 2013, Lee et al 2016, Hoffman et al 2019 and protein interactors (Yang et al 2018, Kekez et al 2019. Thus far, only one crystal structure of plant aaRS is reported (Kekez et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Allelopathic effects of co-cultivation with clover (Pedersen et al 2013), allelochemicals of rice (Kato-Noguchi and Kitajima 2015), and an analog of amino acid (Lee et al 2016), on the growth of A. thaliana have been reported. However, there have been few studies on the allelopathic activity of A. thaliana itself on other plants, except for the slight stimulatory effects of the seed exudates on cockscomb (Yokotani-Tomita et al 1998).…”
mentioning
confidence: 99%
“…43 Studies with Arabidopsis thaliana, a non-Aze-producing plant, indicate that differences in the properties and expression levels of cytoplasmic and organellular ProRSs may render a plant more susceptible to Aze misincorporation. 45 In A. thaliana, the cytoplasmic ProRS mischarges Aze more frequently than the organellular ProRS, making its roots, which produce more cytoplasmic ProRS than its shoots, more vulnerable to Aze toxicity. 45 These differences in ProRS quality control mechanisms thus make Aze an effective means of defense against competing plant species and predators.…”
Section: Discussionmentioning
confidence: 99%
“…45 In A. thaliana, the cytoplasmic ProRS mischarges Aze more frequently than the organellular ProRS, making its roots, which produce more cytoplasmic ProRS than its shoots, more vulnerable to Aze toxicity. 45 These differences in ProRS quality control mechanisms thus make Aze an effective means of defense against competing plant species and predators. 43,45 Prior to the present study, the only family of single domain trans-editing proteins known to target tRNAs misacylated with NPAs was the D-aminoacyl-tRNA deacylases (DTDs), which deacylate D-aa-tRNAs that form due to the inability of some ARSs to preferentially select the L-enantiomer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation